An overview of unbalance compensation techniques using power electronic converters for active distribution systems with renewable generation. (June 2020) - Rafi, Fida Hasan Md; Hossain, M.J.; Rahman, Md Shamiur; Taghizadeh, Seyedfoad
Abstract: In many residential and commercial low voltage (LV) networks, three-phase four-wire distribution systems are used to accommodate single- and three-phase customer loads and renewable energy sources (RES). Unequal distribution of both linear and nonlinear loads, along with the increasing penetration of RES units in distribution networks can increase the neutral current severely and also cause associated voltage unbalance problems, such as neutral to ground voltage rise, neutral voltage shift and harmonics at the point of common coupling (PCC) where grid, loads and converter are linked together. A high neutral current can cause electrical safety concerns at customer points. It also demands a costly neutral conductor with higher current ratio to avoid damages of the conductor and the distribution transformer. Therefore, reducing the neutral current using a control-based compensation method is desirable without increasing the size of the neutral conductor. This paper presents a comprehensive review for reduction of neutral current on different state of the art techniques utilised for power electronic converters having direct and indirect control over unbalance components to compensate for various unbalance effects, such as high neutral current, phase unbalance, and neutral shift, in three-phase four-wire (3 P–4W) LV networks. Relevant international standards and analytical results for unbalanced real LV networks, and load data are also presented. This review provides a clear picture of state of art neutral compensation techniques to identify the challenges and future directions for researchers and engineers working with various RESs in both residential and commercial 3 P–4W LV networks. Highlights: To present a review on reduction of neutral current on different state of the art unbalance compensation techniques. Power electronics based compensation techniques are presented to compensate the neutral current. Different international standards and analytical results are thoroughly analysed. Future directions are put forward which will be useful for engineers working with renewable energy.